Limbic Activation During Cue-Induced Cocaine Craving - Childress, Anna Rose (1999)
OBJECTIVE: Since signals for cocaine induce limbic brain activation in animals and cocaine craving in humans, the objective of this study was to test whether limbic activation occurs during cue-induced craving in humans. METHOD: Using positron emission tomography, the researchers measured relative regional cerebral blood flow (CBF) in limbic and comparison brain regions of 14 detoxified male cocaine users and six cocaine-naive comparison subjects during exposure to both non-drug-related and cocaine-related videos and during resting baseline conditions. RESULTS: During the cocaine video, the cocaine users experienced craving and showed a pattern of increases in limbic (amygdala and anterior cingulate) CBF and decreases in basal ganglia CBF relative to their responses to the nondrug video. This pattern did not occur in the cocaine-naive comparison subjects, and the two groups did not differ in their responses in the comparison regions (i.e., the dorsolateral prefrontal cortex, cerebellum, thalamus, and visual cortex). CONCLUSIONS: These findings indicate that limbic activation is one component of cue-induced cocaine craving. Limbic activation may be similarly involved in appetitive craving for other drugs and for natural rewards.